Adaptation of The Family Health Scale In The Indonesian Context - Margaretha Sih Setija Utami; Maria Bramanwidyantari; Damasia Linggarjati Novi Parmitasari; Flaviantius Febriano Iko; Ellena Ayu Susanto (PSIKODIMENSIA Kajian Ilmiah Psikologi, 2026)
Family health is extremely important because a family is the smallest community in which each member learns about healthy living. Therefore, a valid and reliable family health measurement tool that is cross-cultural is essential for understanding the state of family health worldwide. This study aims to adapt and test the psychometric properties of the Family Health Scale in the Indonesian context. The sampling technique used in this study was incidental sampling, distributed via social media, and completed by 1,843 participants. The validity test results using Average Variance Extracted (AVE) ranged from 0.289 to 0.628, while the Composite Reliability (CR) values ranged from 0.759 to 0.944. The results of the Confirmatory Factor Analysis showed that the Indonesian Family Health Scale model fit the data, with χ²(319) = 1119, p .001; CFI = 0.972; TLI = 0.966; RMSEA = 0.0369 [90% CI: 0.0345; 0.0392]; SRMR = 0.0369; AIC = 112.974. The tested model shows that the four original dimensions of the instrument can be maintained, and that modifying the model through item reduction yields stronger statistical measures without altering the essence of the original dimensions. Based on these results, the Indonesian version of the Family Health Scale can be used as a family health measurement tool.